Production et travail dans les villes à la fin du Moyen Age - Braunstrein, Philippe (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Departing from the application of the concept of industry to medieval economy, this article presents some possible approaches to the subject matter of production and work in the Middle Ages. In the organisation of the productive sectors, special emphasis is given to the leather sector, pointing out comparisons between three cities (Pisa, Freiburg and Cologne). One highlights the technical innovations (in the fustian industry and in the printing press) and the importance of water to siderurgy and textile production, as well as the urban impact that stemmed from the entire industrial development of the late Middle Ages. Finally, one stresses the importance of the complementarity existing between city and surrounding region, proposing also an approach to the different aspects related to the social dimension of work.